Contested Collective Administration of Intellectual Property Rights in Music : The Challenge to the Principles of Reciprocity and Solidarity - Wallis, Roger and Baden-Fuller, Charles and Kretschmer, Martin and Klimis, George Michael (European Journal of Communication, 1999)
Individual intellectual property right holders in music cannot easily enforce their statutory claims to exclusive usage and remuneration. Since the middle of the 19th century, composers and publishers have responded by creating collective bodies, so-called collecting societies which monitor musical activity in a given territory, and collect and distribute fees accordingly. These societies, first established in Western Europe, operate on two principles: the principle of reciprocity, linking monopolistic national societies and the principle of solidarity, making a collecting service available to all right holders at roughly the same rate. The rise of the global media corporation combined with new digital production and distribution technologies has seriously undermined these principles. The article reports recent trends drawing on over 30 interviews with executives of the five largest multinational music firms and the major copyright institutions in Germany, Japan, Sweden and the UK, including the European Commission, the World Intellectual Property Organization and national and international trade bodies. We conclude that the present structure of music copyright is likely to collapse, skewing the distribution of revenues in favour of big corporate players and global musical products if there is no institutional intervention. Policy implications are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjY3MzIzMTk5MDE0MDAxMDAx